(untitled) (Research, Society and Development, 2020)
The edible part of the cashew, the pseudofruit, is considered a residue originated from the nut processing industry. At the end of the process, it is estimated the generation of up to 90% of this residue, however, it is a highly nutritious and complex matrix which has great use potential. One of the most common and feasible ways for this use is the production of cajuína, a traditional drink much appreciated in the Brazilian’s Northeast region, which is obtained from the clarification of the juice extracted from the peduncles of the cashews. After being listed as a Brazilian Cultural Heritage of Traditional Production and Sociocultural Practices, in 2014, in Piauí, the cajuína has been gaining visibility in other states and regions. The increase in consumption and the need to maintain quality and safety of the drink, boosted the preparation of this work, which aims to identify the main hazards in the production of cajuína and how to control them according to the HACCP (Hazard Analysis and Critical Control Points). This review was written taking into account scientific articles, theses and dissertations available in the database. The hazards were identified according to their nature as chemicals - residue from pesticides; physicals - strangers and glass fragments; and biologicals - arising from bacterial contamination throughout the production of the drink. After hazards identification, preventive measures, forms of control and verification were developed based on literature reviews. Thus, it appears that it is possible to implement the HACCP in the processing of cajuína.